Approaching the Bible in medieval England - Poleg, Eyal (Manchester medieval studies., 2013)
Traces how the Bible came to be known by lay people through different mediums. It brings together intellectual and religious history with art history, music, literature and social history to trace how the Bible was sung and preached, revered and studied in thirteenth- and fourteenth-century England.